Spelling of Borrowed Socio-Political Words in Kabardino-Cherkess Language - K. C. Zhiletezhev (Научный диалог, 2018)
The article deals with some issues of spelling in the Kabardino-Cherkess language of socially-political words borrowed from the Russian language or through the Russian language. It is noted that over the past decades the vocabulary of the Kabardino-Cherkess language have a lot, a large number of borrowed words, especially of socio-political meaning, appeared. It is shown that the main source of development and enrichment of socio-political vocabulary of the Kabardino-Cherkess language is the Russian language. The relevance of the study lies in the fact that with such a large number of borrowings in the modern Kabardino-Cherkess language there is no uniformity in the writing of socio-political lexemes. The author analyzes the main disadvantages of the current rules of spelling. The novelty of the research is seen in the fact that the author suggests specific ways to overcome spelling instability in spelling of borrowed socio-political words. It is concluded that the current “Rules of spelling and punctuation of the Kabardino-Cherkess language” need to be reformed, it is necessary to develop scientific principles of spelling of borrowings in the Kabardino-Cherkess language. To solve this problem, it is proposed to establish a linguistic and terminological Commission in the Republic at the government level.